Subsídios para Gerenciamento de Segurança, Meio Ambiente e Saúde: Uma proposta aplicada ao Gerenciamento de Projetos - Otero, Fernando José Ramos (2008)
Recently, Sustainability Issues are increasingly heard about, in particular the importance of the Environment, such as Global Warming, use of natural resources, etc., Social Responsibility and Safety with Work life balance. However, there are some questions regarding the financial feasibility and the return on investments in these areas so that they remain in the second plan in the Production Process. In the same proportion, the increased competition, the global market and the philosophy of producing more with less contribute to the constant improvement of methodologies and management s tools and techniques. It can be said that the Project Management discipline, as Management Support, has been used as an important mechanism for achieving successful results, especially after the PMI Project Management Institute disseminate their guidelines and guidance on this matter, worldwide. This study aims to highlight the need to complement the current methodology adopted for the Project Management, introducing subsidies for integrating HSE Management Safety, Environment and Health to this area of knowledge. In addition to the scope of this study, the author hopes that such work can give greater visibility to this issue and its relation to Management Practices, in order to encourage further studies.